Madžarska v luči obiska turistov iz Slovenije - prostorska razporeditev turističnega prometa in spletne ponudbe - Koderman, Miha (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2017)
The article examines the main characteristics of tourist visits of Slovenians to Hungary. Authors first present an overview of the statistic indicators, where a special emphasis is given to the Slovenian tourists and their role among other international visitors. The second part of the article summarizes the main findings of the analysis of the internet-based tourist services (organized tourist trips), provided by Slovenian travel agencies. The services were subject of spatial and contextual (frequency of the advertised destinations, type of service, duration and price) analysis.
Keywords: Hungary; Madžarska; Slovenci; Slovenes; tourism; turistična geografija; turistična ponudba; turistične destinacije; turizem